INDONESIA’S DEVELOPMENT STRATEGY: THE PATH OF STATE OWNED ENTERPRISES GLOBAL EXPANSION - Bachtiar, Farahdiba Rahma (Global: Jurnal Politik Internasional, 2024)
Following the Asian Crisis, many believed that the era of the developmental state model had ended. However, amidst debates of pros and cons, there was a strong tendency to observe that, before the Jokowi administration, several Indonesian government policies were highly interventionist. This article examines the possibility that the developmental state model will no longer continue in Indonesia, which is merely a myth. Using a qualitative research approach that draws on various literature, including data from 2022–2024 and field research findings in Indonesia during the 2015–2021 period, this article argues that the developmental model has evolved toward a more practical and pragmatic approach. However, this article takes a different perspective than previous literature on Indonesia's developmental state model. By focusing on state-owned enterprises (SOEs) such as PT Perkebunan Nusantara, PT Semen Indonesia, and PT Pertamina, the article highlights three main points: first, the formation of holding companies enables SOEs to become strong economic players; second, the ambition behind the creation of these holdings is political; and third, the expansion trend reflects the government’s commitment to strengthening the role of SOEs in national development. These three points indicate that Indonesia has transformed into a neo-developmental state model, at least since the SBY administration, followed by Jokowi. Ultimately, although the global expansion policy faces challenges, this does not signify the failure of Indonesia as a developmental state.